PEMBERDAYAAN KELOMPOK TANI SEBAGAI PUSAT PELATIHAN PADI ORGANIK YANG PROFESIONAL DAN MANDIRI DI KABUPATEN SRAGEN - Hanifah Ihsaniyati; Suwarto Suwarto; Eny Lestari; Suminah Suminah; Widiyanto Widiyanto; Dwiningtyas Padmaningrum; Retno Setyowati (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2015)
In order to develop a group of partners into a training center professional and independent , need to strengthen the partner groups into the training center of organic agriculture with emphasis on curriculum guides , modules teaching materials , folder teaching materials , and a CD of teaching materials , training management professional , promotional activities , and management financial well done . To that end, it is in this activity try to help reproduce CDs necessary teaching materials , training " campaign management and marketing " training " media creation in the form of website promotion . Results of activity showed an increase motivation, knowledge promotion, marketing , the ability of farmers to make the promotion of online media (website), the drafting of a media campaign (website ) that pelatihanorganik.com and lumbungberasorganik.com , and propagation of teaching materials ( CD ) .